(untitled) (Mustansiria Dental Journal, 2018)
Denture related stomatitis is an inflammatory process that mainly involves the palatal mucosa when it is covered by complete or partial dentures; it appears frequent among denture wearer and varies widely. Fifty patients were examined in this study, 66% of them had denture stomatitis. This study aimed to evaluate the presence of denture stomatitis in denture wearers’ patients, and to know the relation between denture age, denture hygiene, and denture cleansing with denture stomatitis. Results of the present study showed that poor denture hygiene was associated with high percentage of denture stomatitis. Also low percent of denture stomatitis appeared in the denture wearers of 3-4 times/ day denture cleansing. The percentage of reduction in the prevalence of denture stomatitis was clear in newly or less years wearing dentures.